(untitled) (International journal of medical sciences, 2026)
The article presents the results of a study of acid-dependent diseases - gastroesophagealreflux disease, chronic gastritis and peptic ulcer of the stomach and duodenum, age andgendercharacteristics of the disease and their relationship with the genotypes of the virulent Ice AgeneofH. pylori infection. It has been established that acid-related diseases are more often registeredinmen aged 41 to 60 years, in addition, acid-dependent diseases are more often associatedwiththeIce A1/Ice A1 genotype of the Ice A gene of H. pylori bacteria.